Knowledge and willingness to pay for social health insurance scheme among marginalized adults of Lulang, Myagdi. - Pun,Insha (2018)
ABSTRACT: The Social Health Security Scheme under Social Health Protection plan of World Health Organization is a newly launched programme in Nepal that aims to increase the access of health services to the poor, the marginalized, and people in hard to reach areas of the country. So the objective of the study was to examine the Knowledge and Willingness to pay for Social Health Insurance Scheme among the marginalized adults of Lulang in Myagdi district. A Descriptive cross-sectional study was carried out among 98 adults. Non- probability purposive sampling technique was used and the interview was continued until the required sample size was achieved. Semi-structured interview technique was used to collect data. The Willingness to pay was estimated through a Contingent Valuation Method. Obtained data were analyzed using descriptive statistics including percentage, frequency, mean, standard deviation and inferential statistics including Fisher's exact test. The findings revealed that 94.9% had inadequate knowledge whereas, 95.9% were Willing To Pay for proposed SHIS, and the average amount that they were willing to contribute per annum per household was NRs. 1135.64 (11 US $). Respondent's knowledge level was statistically significant with sex and occupation, similarly the status of willingness to pay was statistically significant with education level, household income, and past history of financial hardship while paying medical bills. In conclusion, this study finding suggests that almost all the respondents had inadequate knowledge and an overwhelming number of them were Willing to pay for proposed Social Health Insurance Scheme. The average amount that respondents were WTP was nearly half of the premium amount that Government of Nepal has stated. So, it is recommended that a comprehensive sensitization and awareness programme be conducted and that the premium amount for marginalized and hard to reach areas of our country be devised as per their capacities. Keywords: Social Health Insurance Scheme, Willingness to pay, Marginalized adults, Myagdi.